2018
DOI: 10.1111/jcmm.13622
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cells facilitate the up‐regulation of miR‐153‐3p, whereby attenuating MGO‐induced peritoneal fibrosis in rats

Abstract: MiRNAs contribute greatly to epithelial to mesenchymal transition (EMT) of peritoneal mesothelial cells (PMCs), which is a crucial step in peritoneal fibrosis (PF). In this study, we tried to profile whether miRNA expression differences exist after human umbilical cord mesenchymal stem cells (hUCMSCs) treatment in PF rats and investigate the possible role of miR‐153‐3p involved in anti‐EMT process. We randomly assigned 34 rats into three groups: control group (Group Control), MGO‐induced PF rats (Group MGO) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…SIRT1 overexpression reduces TGF-β-induced extracellular matrix expression and production; in contrast, SIRT1 knockdown promotes renal function damage and enhances renal fibrosis [25]. A similar protective effect of SIRT1 was reported by another group, the authors demonstrated that SIRT1 inhibits EMT by deacetylating Smad4 and suppresses the activation of the TGF-β pathway in human endothelial cells [26]. And a combination of stem cell therapies and biotechnology is one of the present promising fields in tissue damage and wound healing.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…SIRT1 overexpression reduces TGF-β-induced extracellular matrix expression and production; in contrast, SIRT1 knockdown promotes renal function damage and enhances renal fibrosis [25]. A similar protective effect of SIRT1 was reported by another group, the authors demonstrated that SIRT1 inhibits EMT by deacetylating Smad4 and suppresses the activation of the TGF-β pathway in human endothelial cells [26]. And a combination of stem cell therapies and biotechnology is one of the present promising fields in tissue damage and wound healing.…”
Section: Introductionsupporting
confidence: 60%
“…Passage 6 hUCMSCs (1 × 10 6 ) were stained with anti-CD34, CD45, CD90, and CD105 antibodies (1:500; BD Biosciences, San Diego, USA) for 30 min at room temperature. Flow cytometry (Gilson, Middleton, WI, USA) was used to analyze antibody binding and cell surface markers' expression as described previously [26].…”
Section: Isolation Culture and Identification Of Hucmscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, both miR-199a-5p and miR-214-3p were found to target claudin-2 and E-cadherin (E-cad) mRNAs to promote high glucose-induced peritoneal fibrosis in PD (12). In addition, human umbilical cord mesenchymal stem cells facilitate the up-regulation of miR-153-3p, which is a critical molecule in attenuating methylglyoxal-induced peritoneal fibrosis in rats (13). Specifically, miR-21 was shown to promote the progression of peritoneal fibrosis through activating the TGF-␤/Smad signaling pathway in in vivo and in vitro experiments (14).…”
Section: Peritoneal Fibrosis Is a Common Complication Of Long-term Pementioning
confidence: 99%